Anterior Circulation Thrombectomy in Patients With Low National Institutes of Health Stroke Scale Score: Analysis of the National Inpatient Sample - Karan Patel; Kamil Taneja; Liqi Shu; Linda Zhang; Yunting Yu; Mohamad Abdalkader; Matthew B. Obusan; Shadi Yaghi; Thanh N. Nguyen; Negar Asdaghi; Solomon Oak; Daniel A. Tonetti; et al. (Stroke: Vascular and Interventional Neurology, 2024)
Background Prior studies have shown benefit for endovascular therapy (EVT) in patients with large‐vessel occlusion and severe deficits, as captured by the National Institutes of Health Stroke Scale (NIHSS). However, the benefit of EVT in patients with NIHSS score of <6 is unclear. Methods We queried the National Inpatient Sample (2018–2020) for patients with a large‐vessel occlusion of the internal carotid or middle cerebral artery with an NIHSS score of <6, and compared outcomes between patients treated with EVT versus best medical management, using propensity score matching. The primary outcome was routine discharge (home or self‐care). Secondary outcomes were in‐hospital mortality, intracerebral hemorrhage, and length of stay. Primary and secondary outcomes were evaluated using multivariable regression adjusted for baseline characteristics, stroke severity, and treatment with thrombolysis. Results Of the 212 515 patients with an internal carotid artery/middle cerebral artery stroke, 49 115 met the inclusion criteria for our study. There were 3490 (7.1%) patients treated with EVT and 45 625 (92.9%) treated with best medical management. Patients treated with EVT had no difference in ofdds of routine discharge (adjusted odds ratio (OR), 0.99; 95% CI, 0.82–1.19; P = 0.91), but there were longer lengths of hospital stay (adjusted β, 1.26; 95% CI, 0.78–1.74; P<0.001) and higher rates of death (adjusted OR, 2.11; 95% CI, 1.20–3.70; P = 0.01), compared with patients treated with best medical management. In multivariable models, intravenous thrombolysis was independently associated with higher odds of routine discharge (adjusted OR, 1.78; 95% CI, 1.57–2.01; P<0.001) and shorter hospital stay (adjusted β, −0.41; 95% CI, −0.63 to −0.19; P<0.001), but no difference in in‐hospital mortality (adjusted OR, 0.70; 95% CI, 0.39–1.24; P = 0.22). These relationships persisted in the propensity‐matched cohort. Conclusion Patients treated with EVT compared with best medical management had worse clinical outcomes, and this may be attributable to residual confounding (eg, deterioration following an initially low NIHSS score) or procedural factors. Patients treated with intravenous thrombolysis had greater odds of routine discharge. Our findings suggest potential real‐world benefits for intravenous thrombolysis in patients with occlusion of the internal carotid artery/middle cerebral artery and low NIHSS score.